A Agressão Russa à Ucrânia e o Direito Internacional - Pereira Coutinho, Francisco (2023)
The political destiny of Ukraine is framed by Vladimir Putin’s autocratic regime has having an existential nature for the survival of the Russian nation-state. In this ultra-nationalistic rhetoric, international law loses any effective conformative power. International law has been instrumentally subverted for political purposes to systematically justify and legitimate the acts of the Russian State in Ukraine, from the aggression initiated on 24 February 2022 to the territorial annexations concluded on 30 September 2022. These annexations were the legal crux of the Ukrainian tragedy, signaling the armed conflict’s point of no return by crystalizing conflicting territorial claims between Russia and Ukraine.